G.I. nightingales : the Army Nurse Corps in World War II - Tomblin, Barbara B. (Univ. Press of Kentucky, 1996)
The women of the Army Nurse Corps saw the horrors of battle on every front during the Second World War; and their experiences in the various theaters were highly diverse. While those serving in the South Pacific were forced to trade their nurses' uniforms for combat fatigues in order to protect themselves from malaria-carrying mosquitoes, women on the Italian and North African fronts faced constant water shortages and worked dangerously close to battle lines. Nurses in